High-performance kerb with high salt freezing resistance and high flexural tensile strength

By using CFB ash slag and CFB furnace slag to replace fiber and gas induction agent, combined with cement and rice stone, curbs with high salt-resistant freezing and high bending tensile strength are prepared, which solves the high cost problem in the existing technology and achieves performance Improve and reduce costs.

CN119263710APending Publication Date: 2025-01-07SHANXI LUQIAO DEV & CONSTR CO LTD

Patent Information

Application Number
CN202411258515.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, the flexural strength of curbs is improved by incorporating fibers and adding gas inducing agents to enhance the salt freezing performance, resulting in excessive cost problems.

Method used

CFB fly ash and CFB slag are used as the main raw materials, combined with cement, machined sand and rice stone, curbs are prepared through vibrating extrusion process. The self-hardening and porous properties of CFB ash slag replace some fibers and gas induction agents to improve bending resistance and anti-salt freezing properties to reduce production costs.

Benefits of technology

The curb with high salt-resistant and high bending tensile strength has been achieved. The 28d bending tensile strength reaches 8.0MPa, which reduces production costs and meets the performance requirements of the GB20899-2016 "Concrete Curb" standard, while avoiding fiber and induction Use of gas agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of coal-based solid waste resource utilization, and particularly relates to a high-performance kerb with high salt freezing resistance and high flexural tensile strength, which comprises a cementing material, a fine aggregate, a coarse aggregate and water, the cementing material is cement and CFB fly ash, the fine aggregate is CFB slag and machine-made sand, the coarse aggregate is 3-5mm granite and 5-8mm granite, and the water is water. Comprising the following components in parts by weight: 113 to 245 parts of CFB fly ash, 225 to 809 parts of CFB slag, 506 to 613 parts of cement, 383 to 858 parts of machine-made sand, 338 to 417 parts of granite of 3 to 5mm, 338 to 417 parts of granite of 5 to 8mm and 173 to 240 parts of water, and 2450 parts of the CFB fly ash, the CFB slag, the cement and the granite are taken as the total base number. According to the curb, on one hand, resource utilization of solid waste can be achieved, and on the other hand, the production cost of the curb can be reduced; by utilizing the characteristics of self-hardening, volcanic ash activity and micro-expansibility of CFB ash, the CFB fly ash is used for replacing an expanding agent or expansive cement to compensate the shrinkage of the curb; secondly, the fineness modulus of the CFB slag is in a medium sand range, part of machine-made sand is replaced, closed holes are formed in the kerb, the salt freezing resistance of the kerb is improved, and cellulose and an air entraining agent do not need to be added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a curbstone, in particular to a curbstone with high salt freezing resistance and high bending tensile strength, and belongs to the technical field of resource utilization of coal-based solid waste. Background Art

[0002] CFB ash (including CFB fly ash and CFB slag) is an industrial solid waste produced by circulating fluidized bed boiler technology using inferior fuels such as coal gangue, lignite, and coal slime. While using inferior fuels brings huge economic benefits, the amount of slag discharge also increases significantly. The large amount of CFB ash stored, while occupying land, will pollute the environment, cause ecological damage, and affect human health. In addition, the environmental protection tax generated by solid waste discharge has caused a huge economic burden on enterprises. Therefore, the way to utilize CFB ash resources needs to be expanded urgently.

[0003] The existing technology of using vibration extrusion to prepare the curbstone still has certain defects. First, the flexural strength does not reach C f 8.0MPa. The conventional practice is to add fibers to improve its flexural strength, which leads to excessively high costs. Secondly, the curbstones prepared by the existing technology have poor salt-freezing resistance. Adding air-entraining agents to enhance their salt-freezing resistance will also increase costs. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance curbstone with high salt-freezing resistance and high bending and tensile strength, so as to solve the problem in the prior art of increasing the bending strength of the curbstone by adding fibers and enhancing the salt-freezing performance by adding air-entraining agents, which leads to excessively high costs.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: A high-performance curbstone with high salt and frost resistance and high flexural tensile strength comprises a cementitious material, a fine aggregate, a coarse aggregate and water, wherein the cementitious material is cement and CFB fly ash, the fine aggregate is CFB slag and machine-made sand, the coarse aggregate is 3-5 mm stone and 5-8 mm stone, and the curbstone comprises the following components in parts by weight: 113-245 parts of CFB fly ash, 225-809 parts of CFB slag, 506-613 parts of cement, 383-858 parts of machine-made sand, 338-417 parts of 3-5 mm stone, 338-417 parts of 5-8 mm stone, and 173-240 parts of water, with 2450 parts as the total base.

[0006] Preferably, the Fe2O3 content in the CFB fly ash and CFB slag is 6.0%-9.0%, and the SO3 content is less than or equal to 7.0%.

[0007] Preferably, the Fe2O3 content in the CFB fly ash and CFB slag is 9.0%.

[0008] Preferably, the CFB fly ash has a specific surface area of ​​400-500 m 2 / kg.

[0009] Preferably, the CFB slag is raw slag with a fineness modulus ranging from 2.1 to 2.5.

[0010] Preferably, the strength grade of the cement is 42.5.

[0011] Preferably, the 3-5 mm stone and the 5-8 mm stone are continuously graded stones with a particle size of 3-8 mm.

[0012] The main raw materials of the curbstone produced by the technical solution of the present invention include CFB fly ash, CFB slag, cement, machine-made sand, 3-8mm stone and water. CFB ash slag itself has self-hardening and volcanic ash activity, among which CFB fly ash is more active than fly ash and has micro-expansion. In an alkaline environment, its early activity can be stimulated; CFB slag is used as fine aggregate with a crushing value of 25%, which can replace part of the machine-made sand. Adding CFB ash slag to the curbstone can not only save a lot of cement and machine-made sand, but also compensate for the shrinkage of the curbstone. At the same time, CFB ash slag is loose and porous, forming closed holes in the curbstone, similar to the role of air entraining agent, improving its salt-freezing resistance. The Fe2O3 content of CFB ash slag used in this application is 9.0%, which improves the flexural tensile performance of the curbstone to a certain extent. Therefore, CFB slag is of great significance to the flexural tensile strength and salt-freezing resistance of the curbstone.

[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The CFB fly ash and CFB slag used in the present invention are industrial wastes, wherein CFB fly ash replaces part of cement, and CFB slag replaces part of machine-made sand to prepare curbstones through a vibration extrusion process, which can realize resource utilization of solid wastes on the one hand, and reduce the production cost of curbstones on the other hand; (2) The present invention firstly utilizes the characteristics of self-hardening, volcanic ash activity and micro-expansion of CFB ash to replace the expansion agent or expansion cement with CFB fly ash, thereby improving the initial strength of the curb and compensating for the shrinkage of the curb; secondly, the fineness modulus of CFB slag is in the medium sand range to replace part of the machine-made sand, and at the same time, utilizes its loose and porous characteristics to form closed holes in the curb, similar to the role of air entraining agent, thereby improving its salt freezing resistance. The curb does not need to add cellulose and air entraining agent, which is an innovation of the traditional curb component. At the same time, CFB slag is original slag, and no other reagents need to be added, thereby reducing the production cost; (3) The Fe2O3 content in the CFB fly ash and CFB slag used in the present invention is 6.0%-9.0%, and its activity index is higher than that of fly ash. In the process of hydration reaction, more tetracalcium aluminoferrate gel is generated. This gel has good bonding ability and durability, and improves the flexural and tensile strength of cement concrete components. In addition, this gel can also react with other substances in cement to generate a certain amount of hard substances, which is beneficial to improve the durability and compressive strength of cement concrete, and to a certain extent improve the flexural and tensile properties of curbstones. However, the Fe2O3 content must be controlled, otherwise the volume of tetracalcium aluminoferrate crystals in the hydration reaction will be too large, which will lead to a decrease in the initial strength of cement concrete. Therefore, CFB ash slag is of great significance to the flexural and tensile strength of curbstones, which is also an innovation that distinguishes it from traditional materials; (4) The amount of CFB fly ash and CFB slag used in the present invention can reach 25%-40% of the total material amount, which can save a lot of cement and machine-made sand, and improve the salt-freezing resistance and flexural tensile strength of the curbstone. The 28d flexural tensile strength reaches 8.0MPa. After 28 times of salt-freezing resistance, the quality loss is almost zero. DETAILED DESCRIPTION

[0014] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0015] The main components of the salt-freezing-resistant and high-flexural-tensile-strength curbstone of the present application are: cementitious materials, fine aggregate, coarse aggregate and water. The cementitious materials are cement and CFB fly ash, the fine aggregate is CFB slag and machine-made sand, the content of CFB fly ash and CFB slag can reach 25%-40% of the total material amount, the cement adopts P.O42.5 Guojin cement; the coarse aggregate is 3-5mm rice stone and 5-8mm rice stone, and 3-8mm continuously graded rice stone is adopted; the water adopts tap water.

[0016] The CFB ash used comes from the industrial waste slag produced by Shanxi Guojin Power Plant. The main chemical components and their mass percentages in the CFB ash are: SiO2 is 36.42%, Al2O3 is 20.20%, CaO is 20.89%, SO3 is 7.0%, Fe2O3 is 9.0%, MgO is 1.35%, and the calcined vector is 5.14%. Before weighing the CFB slag, the super-particle size above 9.5mm must be screened out. Example 1

[0017] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 113 kg of CFB fly ash, 225 kg of CFB slag, 506 kg of cement, 338 kg of 3-5 mm stone, 338 kg of 5-8 mm stone, and 173.3 kg of water.

[0018] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot and mix evenly, then pour in CFB slag, cement, CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Example 2

[0019] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 149 kg of CFB fly ash, 410 kg of CFB slag, 526 kg of cement, 456 kg of machine-made sand, 369 kg of 3-5 mm stone, 369 kg of 5-8 mm stone, and 189 kg of water.

[0020] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot and mix evenly, then pour in CFB slag, cement, CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Example 3

[0021] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 175 kg of CFB fly ash, 623 kg of CFB slag, 546 kg of cement, 563 kg of machine-made sand, 357 kg of 3-5 mm stone, 382 kg of 5-8 mm stone, and 201.9 kg of water.

[0022] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture. Example 4

[0023] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 203 kg of CFB fly ash, 705 kg of CFB slag, 566 kg of cement, 668 kg of machine-made sand, 374 kg of 3-5 mm stone, 402 kg of 5-8 mm stone, and 215.3 kg of water.

[0024] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot, and then pour in machine-made sand, washed sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Example 5

[0025] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 231 kg of CFB fly ash, 765 kg of CFB slag, 586 kg of cement, 765 kg of machine-made sand, 359 kg of 3-5 mm stone, 427 kg of 5-8 mm stone, and 228.8 kg of water.

[0026] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture. Example 6

[0027] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 245 kg of CFB fly ash, 809 kg of CFB slag, 613 kg of cement, 859 kg of machine-made sand, 417 kg of 3-5 mm stone, 441 kg of 5-8 mm stone, and 240.2 kg of water.

[0028] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture.

[0029] The flexural strength, tensile strength and anti-salt-freeze mass loss of the high-performance curbstones with anti-salt-freeze and anti-flexural tensile strength in the above-mentioned embodiments 1-6 were tested, and the relevant performance data are shown in Table 1. As can be seen from Table 1, the maximum flexural strength at 7d in this application reaches 7.60MPa, and the flexural strength at 28d reaches 8.07MPa, which is much higher than the 6.0MPa required in GB20899-2016 "Concrete Curbstone". The maximum compressive strength at 7d reaches 20.4MPa, and the compressive strength at 28d reaches 40.80MPa. After 28 times of ND anti-salt-freeze test, the average mass loss of 28d anti-salt-freeze test is almost zero, which fully meets the requirements of GB20899-2016 "Concrete Curbstone" that the average mass loss rate of the sample after ND28 times of anti-salt-freeze test should not be greater than 1.0Kg / m 2 , the mass loss of any sample is no more than 1.5Kg / m 2Requirements. In addition, since CFB ash is added to the curb, its expansion is tested. Since the CFB ash used in this application has a sulfur content of 7.0%, which is relatively high, when the CFB ash content exceeds 40%, the curb cracks. Therefore, this application only tests the expansion of curbs with a content of less than 40%. After 1d, 2d, 3d, 7d, 14d, 21d, 56d, and 90d expansion tests, the expansion rate of the curb increases rapidly in the first 14d, and tends to be stable after 28d, with a small change in the expansion rate, indicating that the curb has good stability in the later stage. Therefore, this application controls the total amount of CFB slag to be within 40% according to the sulfur content, not only to obtain a high-performance curb with high salt freezing resistance and high flexural tensile strength, but also to avoid the problem of curb cracking due to its expansion.

[0030] Table 1 Flexural strength and salt-freezing resistance mass loss data

[0031] The main components of the salt-freeze-resistant, high-flexural-tensile-strength curbstone of the present application are: cementitious materials, fine aggregate, coarse aggregate and water. Specifically, the cementitious materials are cement and CFB fly ash, and the fine aggregates are CFB slag and machine-made sand; the content of CFB fly ash and CFB slag can reach 25%-40% of the total material amount, and the cement adopts P.O42.5 Guojin cement; the coarse aggregate is 3-5mm rice stone and 5-8mm rice stone, and 3-8mm continuously graded rice stone is adopted; and tap water is adopted.

[0032] The CFB ash used comes from the industrial waste slag produced by Shanxi Guojin Power Plant. The main chemical components and their mass percentages in the CFB ash are: SiO2 is 36.42%, Al2O3 is 20.70%, CaO is 17.89%, SO3 is 6.5%, Fe2O3 is 6.0%, MgO is 1.35%, and the burning vector is 5.14%. Before weighing the CFB slag, the super-particle size above 9.5mm must be screened out. Example 7

[0033] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 113 kg of CFB fly ash, 225 kg of CFB slag, 506 kg of cement, 338 kg of 3-5 mm stone, 338 kg of 5-8 mm stone, and 173.3 kg of water.

[0034] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot and mix evenly, then pour in CFB slag, cement, CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Example 8

[0035] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 149 kg of CFB fly ash, 410 kg of CFB slag, 526 kg of cement, 456 kg of machine-made sand, 369 kg of 3-5 mm stone, 369 kg of 5-8 mm stone, and 189 kg of water.

[0036] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot and mix evenly, then pour in CFB slag, cement, CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Example 9

[0037] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 175 kg of CFB fly ash, 623 kg of CFB slag, 546 kg of cement, 563 kg of machine-made sand, 357 kg of 3-5 mm stone, 382 kg of 5-8 mm stone, and 201.9 kg of water.

[0038] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture. Example 10

[0039] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 203 kg of CFB fly ash, 705 kg of CFB slag, 566 kg of cement, 668 kg of machine-made sand, 374 kg of 3-5 mm stone, 402 kg of 5-8 mm stone, and 215.3 kg of water.

[0040] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into the mixing pot, and then pour in machine-made sand, washed sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curb stone mixture. Embodiment 11

[0041] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 231 kg of CFB fly ash, 765 kg of CFB slag, 586 kg of cement, 765 kg of machine-made sand, 359 kg of 3-5 mm stone, 427 kg of 5-8 mm stone, and 228.8 kg of water.

[0042] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture. Example 12

[0043] To prepare high-performance curbstones with high salt-freezing resistance and high flexural tensile strength, the raw materials and their corresponding masses are as follows: 245 kg of CFB fly ash, 809 kg of CFB slag, 613 kg of cement, 859 kg of machine-made sand, 417 kg of 3-5 mm stone, 441 kg of 5-8 mm stone, and 240.2 kg of water.

[0044] Pour the weighed 3-5mm stone and 5-8mm stone into the mixing pot, and then pour in CFB slag, machine-made sand, cement, CFB fly ash in turn, and stir evenly to obtain a uniform mixture; pour the specified mass of water into the mixer and stir for 30 seconds to obtain a uniform curbstone mixture.

[0045] The flexural strength, tensile strength and anti-salt-freeze mass loss of the high-performance curbstones with anti-salt-freeze and anti-flexural tensile strength in the above-mentioned embodiments 7-12 were tested, and the relevant performance data are shown in Table 2. As can be seen from Table 2, the maximum flexural strength at 7d in this application reaches 7.07MPa, and the flexural strength at 28d reaches 7.67MPa, which is much higher than the 6.0MPa required in GB20899-2016 "Concrete Curbstone". The maximum compressive strength at 7d reaches 18.35MPa, and the compressive strength at 28d reaches 36.80MPa. After 28 times of ND anti-salt-freeze test, the average mass loss of 28d anti-salt-freeze test is almost zero, which fully meets the requirements of GB20899-2016 "Concrete Curbstone" that the average mass loss rate of the sample after ND28 times of anti-salt-freeze test should not be greater than 1.0Kg / m 2 , the mass loss of any sample is no more than 1.5Kg / m 2 Requirements. In addition, since CFB ash is added to the curb, its expansion is tested. Since the CFB ash used in this application has a sulfur content of 6.5%, which is relatively high, when the CFB ash content exceeds 40%, the curb cracks. Therefore, this application only tests the expansion of curbs with a content of less than 40%. After 1d, 2d, 3d, 7d, 14d, 21d, 56d, and 90d expansion tests, the expansion rate of the curb increases rapidly in the first 14d, and tends to be stable after 28d, with a small change in the expansion rate, indicating that the curb has good stability in the later stage. Therefore, this application controls the total amount of CFB slag to be within 40% according to the sulfur content of the CFB slag, not only to obtain a high-performance curb with high salt freezing resistance and high flexural tensile strength, but also to avoid the problem of curb cracking due to its expansion.

[0046] Table 2 Flexural strength and salt-freezing resistance mass loss data

[0047] Comparative Example 1 To prepare high-performance curbstones with high salt-freezing resistance and high flexural strength, the raw materials and their corresponding masses are as follows: 113 kg of CFB fly ash, 225 kg of CFB slag, 506 kg of cement, 338 kg of 3-5 mm stone, 338 kg of 5-8 mm stone, 173.3 kg of water. The main chemical components and their mass percentages in CFB fly ash and CFB slag are: SiO2 is 36.42%, Al2O3 is 19.70%, CaO is 20.89%, SO3 is 7.5%, Fe2O3 is 9.0%, MgO is 1.35%, and the burning vector is 5.14%. Before weighing the CFB slag, the super-particle size above 9.5 mm must be screened out.

[0048] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into a mixing pot and stir evenly, then pour in CFB slag, cement, CFB fly ash in turn, stir evenly to obtain a uniform mixture; pour a specified mass of water into the mixer, stir for 30 seconds to obtain a uniform curb mixture, and the prepared curb is very easy to crack in a short time.

[0049] Comparative Example 2 To prepare high-performance curbstones with high salt-freezing resistance and high flexural strength, the raw materials and their corresponding masses are as follows: 113 kg of CFB fly ash, 225 kg of CFB slag, 506 kg of cement, 338 kg of 3-5 mm stone, 338 kg of 5-8 mm stone, 173.3 kg of water. The main chemical components and their mass percentages in CFB fly ash and CFB slag are: SiO2 is 36.42%, Al2O3 is 20.20%, CaO is 20.09%, SO3 is 7.0%, Fe2O3 is 9.8%, MgO is 1.35%, and the burning vector is 5.14%. Before weighing the CFB slag, the super-particle size above 9.5 mm must be screened out.

[0050] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into a mixing pot and mix evenly, then pour in CFB slag, cement, and CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour a specified mass of water into the mixer, mix for 30 seconds to obtain a uniform curb mixture, and the prepared curb has a flexural strength of 5.6MPa, which is low and does not meet the requirements of "Concrete Curb".

[0051] Comparative Example 3 To prepare high-performance curbstones with high salt-freezing resistance and high flexural strength, the raw materials and their corresponding masses are as follows: 113 kg of CFB fly ash, 225 kg of CFB slag, 506 kg of cement, 338 kg of 3-5 mm stone, 338 kg of 5-8 mm stone, 173.3 kg of water. The main chemical components and their mass percentages in CFB fly ash and CFB slag are: SiO2 is 37.92%, Al2O3 is 21.50%, CaO is 20.89%, SO3 is 7.0%, Fe2O3 is 5.9%, MgO is 1.85%, and the burning vector is 5.14%. Before weighing the CFB slag, the super-particle size above 9.5 mm must be screened out.

[0052] Pour the weighed 3-5mm rice stone and 5-8mm rice stone into a mixing pot and mix evenly, then pour in CFB slag, cement, and CFB fly ash in turn, mix evenly to obtain a uniform mixture; pour a specified mass of water into the mixer, mix for 30 seconds to obtain a uniform curb mixture, and the prepared curb has a flexural strength of 5.2MPa, which is low and does not meet the requirements of "Concrete Curb".

Claims

1. A high-performance curbstone with high salt and frost resistance and high bending and tensile strength, characterized in that: The invention comprises cementitious material, fine aggregate, coarse aggregate and water, wherein the cementitious material is cement and CFB fly ash, the fine aggregate is CFB slag and machine-made sand, the coarse aggregate is 3-5 mm stone and 5-8 mm stone, and comprises the following components in parts by weight: 113-245 parts of CFB fly ash, 225-809 parts of CFB slag, 506-613 parts of cement, 383-858 parts of machine-made sand, 338-417 parts of 3-5 mm stone, 338-417 parts of 5-8 mm stone, and 173-240 parts of water, with 2450 parts as the total base.

2. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to claim 1, characterized in that: The Fe2O3 content in the CFB fly ash and CFB slag is 6.0%-9.0%, and the SO3 content is less than or equal to 7.0%.

3. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to claim 2, characterized in that: The Fe2O3 content in the CFB fly ash and CFB slag is 9.0%.

4. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to any one of claims 1 to 3, characterized in that: The specific surface area of ​​the CFB fly ash is 400-500 m 2 / kg.

5. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to claim 4, characterized in that: The CFB slag is raw slag with a fineness modulus ranging from 2.1 to 2.

5.

6. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to claim 5, characterized in that: The strength grade of the cement is 42.

5.

7. A high-performance curbstone with high salt-freezing resistance and high bending-tensile strength according to any one of claims 2 or 6, characterized in that: The 3-5 mm quartz and 5-8 mm quartz are continuous gradations of quartz with a particle size of 3-8 mm.

Citation Information

Patent Citations

  • Combined structure kerb and preparation method thereof

    CN112811860A

  • Retarded expansive cement prepared from CFB ash and preparation method thereof

    CN116835894A

  • Ash-based anti-crack road concrete and preparation method thereof

    CN118026611A

  • AU2020101816A4

Cited By

  • Preparation method of detoxified fly ash-based high-strength inorganic ecostone

    CN121758138A